Evaluation of the elasticity of yarns in fabrics analysis of the work carried out on - Abdulazizov Shakirjon Abdurashid Ogli (Zien Journals, 2022)
In this article, the optimal strength of the three factors to maximize the penetration of the surface location. and it was determined that the supported surface is observed during the descent.
Keywords: Exploitation; mobility; Mowing; Surface